Dipsticks and point-of-care Microscopy in Urinary Tract Infections in primary care: Results of the MicUTI pilot cluster randomised controlled trial - Peter K. Kurotschka; Martin J. Koch; Eva Bucher; Adolfo Figueiras; Jochen Gensichen; Alexander Hapfelmeier; Alastair D. Hay; Christian Kretzschmann; Oliver Kurzai; Thiên-Trí Lâm; Kathrin Lasher; Orietta Massidda; et al. (PLoS ONE, 2025)
Objectives To evaluate the feasibility of a novel point-of-care test (POCT) management strategy including phase contrast microscopy for bacteriuria and urinary dipsticks for erythrocytes to guide antibiotic prescribing in women with suspected uncomplicated urinary tract infection (uUTI) in general practice. Design Pilot cluster randomised controlled trial in 20 general practices in Germany. Practices were assigned 1:1 to POCT-guided management or usual care. All urine samples were sent for urine culture. Follow-up over 28 days involved symptom diaries, telephone interviews, and medical record review. Outcomes Primary outcomes were recruitment and retention rates. Secondary outcomes included total and inappropriate antibiotic use, symptom duration and burden, recurrent and upper UTIs, re-consultations, and diagnostic accuracy of microscopy versus urine culture. Mixed-effects models accounted for clustering. Results Over 8 months, 157 women were recruited (90 intervention, 67 control), median of 7.5 patients per practice (range 1–15). Participant retention at day 28 was 75%. Baseline characteristics were well balanced. Antibiotic use was similar in both groups: 77% (intervention) vs. 79% (control) at initial consultation. The mean number of antibiotic courses over 28 days was 0.96 (intervention) vs. 1.00 (control), with no indication of reduced prescribing. Phase-contrast microscopy showed limited diagnostic accuracy, especially for ruling out infection (negative predictive value 46%). Exploratory analyses suggested that if GPs had access to urine culture results at the point of care, antibiotic prescribing in the intervention group could have been higher than in routine care. Conclusion The POCT-guided management approach for suspected uUTIs is feasible but presents implementation and methodological challenges. Recruitment varied across sites and was lower in the control group practices, highlighting the risk of differential recruitment. Retention was below the expected 80%, indicating the need for efficient follow-up strategies in future trials. Explorative analyses suggest that simply adding diagnostic information may not support antibiotic stewardship. Novel POCTs should be carefully assessed for their influence on prescribing before routine use. Trial registration: ClinicalTrials.gov NCT05667207.